SOCIAL MEDIA AS A TOOL FOR LANGUAGE LEARNING: FOSTERING LEARNER AUTONOMY AND DIGITAL LITERACY - Odilova Fotimakhon, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This  article  explores  the  transformative  role  of  social  media  platforms  as comprehensive  tools  for  autonomous  language  learning.  In  the  contemporary educational  landscape,  the  shift  from  traditional,  teacher-led  instruction  to  learner-centered agency is facilitated by digital environments. By analyzing the pedagogical potential of platforms like Instagram, YouTube, and Telegram, the study highlights how  "incidental  learning"  and  "digital  literacy"  contribute  to  long-term  linguistic retention  and  communicative  competence.  The  research  argues  that  social  media provides a "customized curriculum" that enhances intrinsic motivation and prepares EFL learners for the complexities of global, real-world communication.